Returns to Office in National and Local Politics - Kaisa Kotakorpi; Panu Poutvaara; Marko Terviö (Institute for the Study of Labor (IZA), 2016)
We estimate the effect of getting elected on future income development of political candidates. We present a bootstrap approach for measuring electoral closeness, which can be used to implement a regression discontinuity design in any electoral system. We apply the method to the Finnish proportional open list system. Being elected to parliament increases annual earnings initially by exteuro20,000, and getting elected to a municipal council by exteuro1,000. The returns to office for parliamentarians accrue mainly through higher wages during the time in office. Our results imply that the returns to office may be large even in the absence of corruption.
Keywords: D72; J45; 330; returns to office; elections; regression discontinuity